Relação entre a presença de macrófagos no microambiente tumoral e fatores prognósticos em câncer de mama - Labre, Luciana Vieira Queiroz (2018)
Introduction: The analysis of possible biomarkers associated with the more aggressive behavior of breast carcinomas, linked to clinical and prognostic information, can provide important data in the treatment of patients with breast cancer. There are indications that the presence of tumor associated macrophages (TAMs) in the tumor microenvironment is associated with a worse prognosis for women with breast cancer. Objective: To evaluate the importance of the presence of macrophages in the tumor microenvironment in breast neoplasms. Methods: This retrospective cross-sectional study included 93 cases of women with invasive ductal breast cancer and submitted to immunohistochemical analysis of the markers for CD68 (M1 / M2) and CD163 (M2) macrophages. The counts of CD68 + and CD163 + cells were performed in a peritumoral region, considering hot spot fields, and the cases under study were classified as low infiltration or high infiltration using semiquantitative evaluation of cell marking. Statistical analysis was performed using the Stata 13.0 program (Stata Corp., College Station, TX, United States), with bivariate analysis, considering the level of significance of p <0.05, and multivariate analysis where the variables with p <0.2 were submitted to the logistic regression test. The Kaplan-Meier method and the log-rank test were used in the analysis of survival curves. Results: High levels of TAMs (CD68 +) were significantly correlated with: patient age, presence of distant metastasis, more advanced tumor staging, absence of estrogen receptors (ER) and progesterone (PR), and triple negative breast cancer (TN). The reduction of the overall survival rate in the cases of women with breast cancer studied was significantly associated with high infiltration of TAMs (CD68 +). The high infiltration of TAMs phenotype M2 (CD163 +) was significantly correlated with the independent variables presence of distant metastasis, absence of RE and TN breast cancer. Conclusions: The association of the analysis of TAM biomarkers with clinical and prognostic information showed that the high presence of macrophagic infiltrate has a significant prognostic value, adding information on the relationship between the presence of macrophages in the tumor microenvironment of cases of women with carcinoma and the clinical-pathological characteristics of the tumor. In addition, TAMs appear as potential prognostic markers for breast cancer.